Liquidity, asset quality, and efficiency to sustainable growth rate for banking at Indonesia Stock Exchange - Syapril Junaidi; Sulastri Sulastri; Isnurhadi Isnurhadi; Mohamad Adam (Jurnal Keuangan dan Perbankan, 2019)
The focus of the bank to increase profit. However, the increase in profit is not important to focus on because the sustainability of growth is more important. Measure the level of sustainable growth is an important factor that needs attention as a reflection for the performance of a bank. The measurement uses the concept of growth called the Sustainable Growth Rate (SGR). This study aims to provide empirical evidence on the effect of liquidity proxy Loan to Funding Ratio (LFR), asset quality proxy by Non-Performing Loan (NPL) and efficiency proxy by Operating Cost to Operating Income (BOPO) toward SGR. The sampling technique is purposive based on the criteria so that the selected 22 banks with the study period 2012-2107. Unit analysis as much as 132 observations. The analysis of data using panel data regression. The findings of the study showed that LFR, NPL, and BOPO had a significant negative effect on SGR. The implications of research that SGR becomes important as it relates to the bank's strategy to continue to grow and continue in order to expand its business maximally while maintaining internal and external funding sources.JEL Classification: G2, G21DOI: https://doi.org/10.26905/jkdp.v23i2.2699